Anime dan Manga di Indonesia Tahun (1990-2006) - Bintang Putra Rachmad; Listi Murnita Krisna; Suryo Ediyono (Universitas Negeri Gorontalo, 2026)
This study examines the development of anime and manga in Indonesia from 1990 to 2006 as part of the spread of Japanese popular culture. The research focuses on the development of anime and manga genres, their distribution media, and public responses in Indonesia toward their presence. This study uses the historical method, including heuristics, source criticism, interpretation, and historiography. The findings show three main phases of development. The first phase (1990–2000) is marked by the introduction of anime and manga through legal print comics and national television broadcasts. The second phase (2001–2005) shows an expansion of genres and audiences, reaching adult consumers. The third phase begins in 2006 with a shift in distribution through the internet, enabling broader access to various types of anime and manga content. This study complements the historical narrative of research into Japanese popular culture in Indonesia between 1990 and 2006, which had previously been limited to the study of culture and developments in the modern era.